The Relationship Between CEO Duality and Business Firms’ Performance: The Moderating Role of Firm Size and Corporate Social Responsibility - Mubeen, Riaqa; Han, Dongping; Abbas, Jaffar; Álvarez-Otero, Susana; Sial, Muhammad Safdar (Frontiers in Psychology, 2021)
This present study focuses on exploring the relationship between chief executive officer (CEO) duality and firm performance. We focus on how firms' size and corporate social responsibility (CSR) moderate this relationship. In terms of size, business organizations are of two types: small and large firms. This study uses the datasets of listed Chinese business firms included in the China Stock Market and Accounting Research database. It employs a generalized method of moment's technique to explore the connection between CEO duality and Chinese business firms' performance through double-mediation effects. Our empirical analysis showed that CEO duality has a significant negative relationship with firm performance. We also explored the moderating effects of firm size (small and large) and CSR practices on the relationship between CEO duality and improved Chinese firms' performance. Large firms and CSR practices showed significant and positive moderating effects on the relationship between CEO duality and firm performance. Conversely, with CEO duality, small firms showed a negative moderating influence on firm performance. This inclusive model provides valuable insights on how the dual role of a firm's CEO affected Chinese firms' performance through the moderating role of CSR practices and firm size for better business performance. The study offers empirical and theoretical contributions to the corporate governance literature. This research framework might help researchers in designing robust strategies to evaluate the effects on firm performance. Researchers may gain helpful insights by using this methodology.